The 21st Century at Work: Forces Shaping the Future Workforce and Workplace in the United States - Karoly, Lynn A. (RAND Corporation, 2004)
What are the forces that will continue to shape the U.S. workforce and workplace over the next 10 to 15 years? With its eye on forming sound policy and helping stakeholders in the private and public sectors make informed decisions, the U.S. Department of Labor asked RAND to look at the future of work. The authors analyze trends in and the implications of shifting demographic patterns, the pace of technological change, and the path of economic globalization.